Fake history. Sobre la manipulación del pasado en Cataluña - Kubiaczyk, Filip (Studia Europaea Gnesnensia, 2023)
This article explores how the past is manipulated in the Catalan national discourse. It outlines main narrative strategies used to exclude that which is Spanish from the image of Catalonia’s past, and discusses the consequences, involving the distortion of historical consciousness among the Catalans.